Cultural reproduction of mental illness stigma and stereotypes. (January 2022) - Jacobs, Susan; Quinn, Joseph
Abstract: This study investigates how schemas and stereotypes about individuals with mental illness shape how information is transmitted between people. Mental illnesses are highly stigmatized identities, and prior work illustrates the persistence of mental illness stigma, despite public health efforts aimed at increasing awareness of the biological origins of mental illness (Pescosolido et al., 2010). Recent work has also demonstrated the utility of combining cultural cognition with social psychological theories of cultural meaning to investigate how stereotypes are transmitted through secondhand narratives (Hunzaker 2014, 2016). We connect this social psychological work with medical sociological literature on mental illness stigmas and propose that stereotypes function as cultural schemas that shape the way stories are remembered and retold about individuals with a mental illness. We then conduct a narrative transmission study to test this proposal, using schizophrenia as a case of interest. Consistent with prior work, we find that individuals who retell a story about a person with schizophrenia alter the narrative so that it becomes more consistent with stereotypes about individuals with schizophrenia. We also find that stereotype-inconsistent information is more likely to be transformed to align with culturally shared beliefs about schizophrenia. The findings extend prior work on how bias shapes the reproduction of mental illness stereotypes, and demonstrate how socially learned cultural beliefs can reinforce stereotypes, biases and stigma about mental illness. Highlights: Schema-consistency bias shapes the information transmitted through narratives. Narratives about schizophrenia become more schema-consistent through retellings. Stereotype-inconsistent information is likely to be transformed. Transformed narrative information tends to become more stereotype-consistent. Schema-consistency bias aids in the reproduction of mental illness stereotypes.